2018
DOI: 10.1186/s12882-018-1135-7
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent glomerulonephritis following renal transplantation and impact on graft survival

Abstract: BackgroundRecurrence of primary glomerulonephritis in the post-transplant period has been described in the literature but the risk remains poorly quantified and its impact on allograft outcomes and implications for subsequent transplants remain under-examined. Here we describe the rates and timing of post-transplant glomerulonephritis recurrence for IgA nephropathy, focal segmental glomerulosclerosis, mesangiocapillary GN and membranous GN based on 28 years of ANZDATA registry transplant data.MethodsWe investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 22 publications
(21 reference statements)
2
32
1
Order By: Relevance
“…Jiang et al conducted a study showing that recurrent GN also depends on male gender, early age, duration on dialysis less than 5 years before transplant; this study confirm that there is no evidence for an increased risk of recurrence in a subsequent graft except for FSGS [ 17 , 18 ]; on the contrary, Ohmacht et al highlight higher risks in IgAN for second graft [ 19 ].…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 71%
See 1 more Smart Citation
“…Jiang et al conducted a study showing that recurrent GN also depends on male gender, early age, duration on dialysis less than 5 years before transplant; this study confirm that there is no evidence for an increased risk of recurrence in a subsequent graft except for FSGS [ 17 , 18 ]; on the contrary, Ohmacht et al highlight higher risks in IgAN for second graft [ 19 ].…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 71%
“…Previous studies report that there is a grown risk of recurrence of IgAN in a subsequent graft [ 55 ]. Conversely, recent studies suggested that there is no increased risk of recurrence on patients who lost the first graft for recurrence [ 18 ].…”
Section: Primary Gn Iga Nephropathy (Igan)mentioning
confidence: 99%
“…The rate of recurrence can be underestimated if all patients who receive a renal transplant do not have a histological diagnosis of the original disease, or if the follow-up after transplant is too short. Recurrence rate reported in the ANZDATA registry for IgAN at 5 and at 10 years were, respectively 5.4% (4.3–6.5) and 10.8% (9.2–12.5%) (4). These data suggest that, recurrence of IgAN is apparently a time dependent event; the longer the follow-up, the higher the probability of recurrence.…”
Section: Incidence Of Igan Recurrence In Kidney Transplantmentioning
confidence: 99%
“…The variable indication to graft biopsy in the different centers is one of the reasons. The rate of IgAN recurrence is higher in studies in which protocol biopsies are performed (5) in comparison to studies that reported graft biopsies done for clinical reasons only (6, 7) and in Registry analysis (4). As a matter of fact, recurrences of IgAN can be “histological only” when diagnosed on protocol biopsies in asymptomatic patients; or “clinical,” when associated with urinary abnormalities and/or graft dysfunction.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation